Dampak Pengelolaan Subak Jatiluwih sebagai Warisan Budaya terhadap Lingkungan - Sri Widari, Dewa Ayu Diyah (Jurnal Kajian dan Terapan Pariwisata, 2021)
The management of Jatiluwih Tourist Attraction which utilizes subak as the main attraction, in addition to being aimed at providing welfare for local communities is also expected to maintain the existence of subak as part of the World Cultural Heritage. The management of Jatiluwih Tourist Attraction as part of the World Cultural Heritage is related to the impact on environmental aspects. Data collection techniques by observation and interview. The interview technique used is an indepth interview conducted with the Head of Village, Bendesa Adat, Pekaseh, Kelian Dusun, Kelian Tempek, Operational Management of Jatiluwih Tourist Attraction. Guided interview techniques are conducted with tourism entrepreneurs and the community. Tourism management has an impact on the decline of water resources and water pollution, air pollution that can affect environmental quality. The construction of tourism facilities that are not in accordance with spatial planning has a negative impact on the environment, namely the loss of landscapes and agricultural land. The management of tourist attractions also has a positive impact on the environment. Environmental cleanliness is increasingly maintained, there are liquid waste reservoirs in tourism businesses. Tourism facilities are built following the landscape of Jatiluwih Village which is procrastinating has an impact on the appearance of the region (visual and aesthetic). Local people maintain the preservation of the forest, animals that live around the Jatiluwih Village area is also maintained. The existence of flora and fauna found is still maintained, in awig-awig Subak Jatiluwih contains the value of local wisdom of biotic environmental preservation. Jatiluwih village has a variety of myths that are believed by the community, the existence of this myth is very instrumental in maintaining the preservation of the natural environment.